Post-*.ism & the Third World: a theoretical reassessment & fragments from Brazil and India - Monte-Mór, Roberto Luis de Melo; Ray, Sumanta (Nova Economia, 2013)
Post-*.ism & the Third World: a theoretical reassessment & fragments from Brazil and India